Hysterectomy and ovarian cystectomy using natural orifice transluminal endoscopic surgery: An initial experience at Tzu Chi General Hospital - Dah-Ching Ding; Tang-Yuan Chu; Mun-Kun Hong (Tzu Chi Medical Journal)
Objectives: The objective of this study is to report our initial experience with patients undergoing transvaginal natural orifice transluminal endoscopic surgery (NOTES). Materials and Methods: From September 2016 to December 2016, patients who were not virgins and did not have pelvic inflammation or obliteration of the cul-de-sac who underwent NOTES hysterectomy or ovarian cystectomy (OC) were included in the study. Results: Transvaginal NOTES was performed smoothly in six patients, two patients (mean age 35 years, mean body mass index [BMI] 25) received an OC and four patients (mean age 49 years, mean BMI 27) underwent a hysterectomy. One patient with a hysterectomy received concurrent adhesiolysis. The mean surgical times were 74 and 75 min and blood loss was 50 and 87.5 ml in the OC and hysterectomy groups, respectively. One patient with a hysterectomy had a postoperative fever with 38°C last for 2 days. Pain scores were 0 at 48 h postoperatively in both groups. Conclusion: Transvaginal NOTES is a feasible and safe technique for hysterectomy and OC in our patients and those in previous reports. This procedure was minimally invasive with no scars on the abdomen as well as little pain.